RELIGIOUS EXTRACURRICULAR ACTIVITIES OF MUSHOLA LOVER STUDENTS IN IMPROVING LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION - Kiflin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
Learning at school is generally given in two forms, namely intracurricular and extracurricular. These two factors can influence student learning outcomes. This research aims to find out how extracurricular activities in the form of Musholla-loving students at school have a positive effect on students' learning outcomes. This research is qualitative and uses SMAN 1 Parigi as the research location. The research sources were five people, consisting of supervisors, two of Musholla lovers students, and teachers. The results of this research found that the extra-curricular activities carried out through the Musholla loving students at SMAN 1 Parigi were divided into four forms of activities: a. daily activities, such as congregational midday prayers, kultum after midday prayers, and cleaning the prayer room; b. weekly activities, such as morning dhikr and yasinan, which are held on Fridays. This activity was followed by a cult c. monthly activities, such as ta'lim and mabit. Mabit activities are marked by staying overnight at school, which contains activities studying the Koran and Hadith, collective dhikr, and evening prayers; d. annual activities, which are divided into spiritual and social activities, such as celebrating Islamic holidays, Islamic boarding school, sharing iftar, and breaking the fast together, as well as social service. Another finding in this research is that students who actively participate in extracurricular activities can fulfill learning objectives as well, especially in semester exams and other formative exams. This shows that extracurricular activities at school can strengthen and improve student learning outcomes, as well as strengthen their social and religious behavior.